Language Learning Strategies, English Motivation, and English Proficiency of Diploma EFL Learners in Malang - Wildha Rosidah (Graduate Program, University of Islam Malang, 2021)
AbstractThis study aimed to measure the relationship between language learning strategies and English motivation toward English proficiency of EFL learners. SILL questionnaire, English motivation questionnaire, and also simple TOEFL test were administered to 37 diploma EFL learners in Malang. All the instruments were administered via G-form in pandemic COVID-19. The SPSS was applied to calculate the multiple regression. The results showed that there were no significant relationship between language learning strategies and English motivation; there were no significant relationship between English motivation and English proficiency; and there were no significant relationship between language learning strategies, English motivation, and English proficiency simultaneously. This results may be useful for understanding the language assessment in measuring students’ ability. To gain deep information, further researcher can combine interview method to measure students’ language learning strategies and English motivation.